Control interno al departamento financiero y su influencia en el cumplimiento de pagos a proveedores de Oriental industria alimenticia O.I.A. S.A. cantón Quevedo, período 2018-2019 - Silva Varela, Evelyn Patricia (2020)
This research was carried out at the Oriental Industria Alimenticia O.I.A. S.A. in the financial area and departments immersed in the process of payments to suppliers. The problem that currently exists is the dissatisfaction of the suppliers in the payments which has diminished the commercial relations and this has generated that sometimes there is no essential raw material component to continue with the production. The objective was to analyze the bill payment procedure, considering its internal process manual for issuing checks and transfers. There is also the need to evaluate the internal control that the company applies to the financial department to know the level of risk, confidence and its impact on payment management. In addition, an analysis was made to the cash flow considering the first flow of each month. The methodology used for the investigation was the descriptive one, qualitative and quantitative studies oriented to have real and pertinent information, to obtain it a questionnaire was applied to the total population, which will allow to know and compare the internal control model applied; Interview with the financial management to evaluate their internal processes and an analysis of the cash flow statements comparing the past due portfolio of suppliers and the actual payments made. The results are based on greater efficiency, which allows speeding up the control, registration and payment processes, in order to maintain an effective relationship with suppliers. Key words: Internal control, Accounting, Finance, Suppliers